Turn-taking Strategies in Jamie Miller’s Interview with Zach Sang Show - Virginia, Fanny (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
This research adopted conversational analysis to investigate the turn-taking strategies, how the strategies were applied, and the dominant strategy. Jamie Miller’s interview with Zach Sang show entitled “Jamie Miller Talks Broken Memories, Here’s Your Perfect, Coming Out, Khloe Kardashian and The Voice” was chosen as the data source. It was published on May 12th, 2022 and generally talked about the singer’s fame whose single “Here’s Your Perfect” has racked millions streams. Observing the data source and typing the conversations were done to collect data. The collected data were further analyzed by using referential identity method and referential competence- in equalizing technique. All processes of this research were in accordance with descriptive qualitative research. The theory invented by Stenstrom (1994) was used to analyze data and transcription symbols theory of Jefferson (2004) was implemented to transcribe the conversations. The results exposed that 78 utterances referred to turn-taking strategies and 11 strategies were employed. The data involved eight data of hesitant start and uptakes, seven data of clean start and uptakes, one data of alerts and giving up, nine data of filled pause and/or verbal fillers, 13 data of lexical repetition, 12 data of prompting, and three data of appealing. From the total data, lexical repetition was found as the dominant strategy. The participants mostly repeated the same lexical items to manage the conversation flow and avoid speech gap.